Independent Tailoring of Super-Radiant and Sub-Radiant Modes in High- Q Plasmonic Fano Resonant Metasurfaces - Soci, Cesare (2017)
Fano resonances in plasmonic metasurfaces arise from the interference between a super-radiant and a sub-radiant plasmon mode. The interference of the plasmon modes, which gives rise to the Fano resonance phenomenon in a plasmonic metasurface, also restricts the independent control of the individual resonance modes. Independent tailoring of super-radiant and sub-radiant plasmon modes at nanoscale is one of the challenges to be addressed for the realization of targeted functionalities and fundamental understanding of plasmon mode coupling. Here, it is experimentally and numerically shown that the spectral position and line-width of both the super-radiant and sub-radiant plasmonic modes of a Fano resonance can be independently controlled through the variation of metal film thickness at the skin depth scale and polarization of the incident light. The metasurface consists of a conductively coupled annular and rectangular aperture array that supports multiple high-Q Fano resonances at near-infrared frequencies. Fano resonances are excited via interference between the azimuthal plasmon mode of the annular aperture and the dipolar plasmon mode of the rectangular aperture. The multiple Fano resonances excited in the proposed design show remarkable sensitivity to skin-depth scale film thicknesses, enabling independent control of spectral position and line-shape of super-radiant and sub-radiant modes in high-Q plasmonic Fano resonant metasurfaces.